Integrating Graffiti into Local Culture-Based Art Education: A Case Study in Surabaya - Sutejo, Aris; Sunarmi, Sunarmi; Soewardikoen, Didit Widiatmoko (Journal of Innovation in Educational and Cultural Research, 2025)
This study addresses the increasing presence of graffiti as a form of urban visual culture that reflects local identity and holds pedagogical potential. It examines the visual characteristics of graffiti created by urban artist crews in Surabaya and explores its integration as an innovative medium in culture-based art education. A qualitative descriptive approach was employed, utilizing an inductive case study method. Data were collected through visual observations at public graffiti sites, semi-structured interviews with artists and art teachers, and online surveys involving teachers and high school students. The findings reveal that Surabaya's graffiti incorporates symbolic visual elements, local narratives, and responses to social and environmental issues. Both teachers and students express a strong interest in graffiti as a relevant and engaging learning medium. The study proposes a practical learning model based on project-based and contextual approaches, emphasizing collaboration, ethical expression, and local cultural awareness. This research contributes to the advancement of art education by offering a structured framework that repositions street-based visual practices as legitimate pedagogical tools. It provides new insights into visual culture education, expands the discourse on culturally responsive teaching, and bridges the gap between informal urban art and formal school-based learning.